M-IAR: Biologically Inspired Routing Protocol for Wireless Multimedia Sensor Networks - Rahman, M.A.; GhasemAghaei, R.; El Saddik, A.; Gueaieb, W. (2008 IEEE Instrumentation and Measurement Technology Conference, 2008)
In this paper, we propose multimedia-enabled improved adaptive routing (M-IAR) that is optimized for single-source-to- single-destination multimedia sensory data traffic. It is an extension of the improved adaptive routing (IAR) algorithm presented in our earlier work, in response to the increasing number of applications incorporating wireless multimedia sensors such as wireless microphones and cameras. M-IAR is a swarm-intelligent- based algorithm exploiting the concept of ant colony optimization to optimize end-to-end delay, jitter, latency, energy consumption, packet survival rate, and routing path, within the multimedia wireless sensor network. The presented algorithm is proven to satisfy its goals through a series of computer simulations.